"Caught between a scream and a hug": Women's perspectives on music listening and interaction with teenagers in the family unit. (September 2015) - Morgan, Jill P.; MacDonald, Raymond A. R.; Pitts, Stephanie E.
There has been considerable research on the emotional and cognitive impact of music in people's everyday lives, but limited attention to its role within relationships, particularly inside the family unit. This article explores the emotional experiences of women in midlife when listening to music, with special reference to their interaction with the musical choices of their adolescent offspring and the bearing this has on their relationships. Ten women aged between 40 and 52 years and their teenage children provided qualitative data through semi-structured interviews which focused on their listening behaviours, expressions of self-identity and uses of music whilst considering each other's musical tastes. This investigation employs a hermeneutic approach and provides new information about the relationship between adolescent musical habits and mother/child dynamics with particular reference to personal and social identity. Mothers were found to enjoy harmonious relationships with daughters through shared musical choices. This was not evident in the information exploring the relationship between mothers and their sons. The article reveals that adolescent musical habits play an important role in influencing the musical listening experiences of mothers.